Beyond economic man: Feminist theory and economics - Ferber, Marianne A.; Nelson, Julie A. (Women's Studies, 1993)
An examination of the central tenets of economics from a feminist point of view. The authors suggest that the discipline of economics could be improved by freeing itself from masculine biases, and raise questions about the discipline's objective nature.
Keywords: OFDIG; approches et analyses; discipline; inégalités; point de vue situé; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie

If women counted: A new feminist economics - Waring, Marilyn (Harper & Row, 1988)
This is a revolutionary and powerfully argued feminist analysis of modern economics, revealing how woman's housework, caring of the young, sick and the old is automatically excluded from value in economic theory. An example of this pervasive and powerful process is the United Nation System of National Accounts which is used for wars and determining balance of payments and loan requirements.
Keywords: OFDIG; approches et analyses; discipline; femmes*; inégalités; sciences de la gestion; systèmes d'oppressions; thématiques; travail; économie